Housing pathways, aspirations and preferences of young adults within increasing urban density. Issue 1 (2nd January 2020) - Opit, Simon; Witten, Karen; Kearns, Robin
Abstract: There is growing recognition within housing preference studies that younger housing consumers are more amenable to compact dwellings. Yet, there remains uncertainty around the drivers of these preferences. In Auckland, the development of a spatial plan emphasizing intensification has attracted opposition from residents, reinforcing a notion that compact housing is largely unappealing. Utilizing a housing pathways approach, we question this notion through examining the housing narratives of Generation Y, a cohort whose preferences are largely ignored in this debate and poorly understood within housing research. This paper highlights the influence of past experiences on attitudes to changing urban environments, providing several themes related to housing experiences that have the potential to influence preferences. We conclude that a process of 'acclimatisation' to density is likely as Generation Y become exposed to higher-density housing. However, to encourage positive experiences, compact dwellings must attend to the dynamic nature of contemporary housing pathways and provide quality housing, located where young people aspire to live.